Biochemical and Computational Approaches to Improve the Clinical Treatment of Dopa Decarboxylase-Related Diseases: An Overview - Cellini, Barbara (Bentham Open, 2012)
Dopa decarboxylase (DDC) is a pyridoxal 5’-phosphate (PLP)-dependent enzyme that by catalyzing the decarboxylation of L-Dopa and L-5-hydroxytryptophan produces the neurotransmitters dopamine and serotonin. The functional properties of pig kidney and human DDC enzymes have been extensively characterized, and the crystal structure of the enzyme in the holo- and apo-forms has been elucidated. DDC is a clinically relevant enzyme since it is involved in Parkinson’s disease (PD) and in aromatic amino acid decarboxylase (AADC) deficiency. PD, a chronic progressive neurological disorder characterized by tremor, bradykinesia, rigidity and postural instability, results from the degeneration of dopamine-producing cells in the substantia nigra of the brain. On the other hand, AADC deficiency is a rare debilitating recessive genetic disorder due to mutations in AADC gene leading to the inability to synthesize dopamine and serotonin. Development delay, abnormal movements, oculogyric crises and vegetative symptoms characterize this severe neurometabolic disease. This article is an up to date review of the therapies currently used in the treatment of PD and AADC deficiency as well as of the recent findings that, on one hand provide precious guidelines for the drug development process necessary to PD therapy, and, on the other, suggest an aimed therapeutic approach based on the elucidation of the molecular defects of each variant associated with AADC deficiency.